Analysis of Viscosity Effects from the Addition of Mesona Palustris (Black Grass Jelly) on Chitosan Polymer - Mohamad Obby Adianto; Muhammad Agni Gustama; Ferdian Budi Ar Rouf; Nyimas Ulfatry Utami; Robekca Purba (Tinta Emas Publisher, 2025)
The main purpose of polymer injection is to reduce the water-oil mobility ratio. Polymers that are widely used are polyacrylamide and polysaccaharides. By increasing the viscosity of the injection fluid, polymer injection can increase the sweep efficiency thereby increasing oil recovery. Refining on petroleum is highly dependent on the efficiency of macroscopic and microscopic pressing. This research purpose is to determine whether the viscosity effect resulted from mesona palustris addition on chitosan polymers could make a good viscosity for oil recovery. The method used in this research is a laboratory experiment with an Ostwald viscometer. The salinity of the formation water used in this study was 20.000 ppm with variations in polymer concentrations of 500 ppm, 1.000 ppm, and 2.000 ppm on the polymer without a mixture of mesona palustris and with a mixture of mesona palustris. The results showed that there was a decrease in polymer viscosity with the addition of mesona palustris to the chitosan polymer, namely the polymer concentration of 500 ppm decreased from 1,56 cp to 1,04 cp, the polymer concentration of 1.000 ppm decreased from 1.87 cp to 1.21 cp. And at a polymer concentration of 2.000 ppm it decreased from 2.38 cp to 1.43 cp.